Empowering Marginal and small-scale farmers in Tamil Nadu, India Through Sustainable Organic Farming: a Pathway to Livelihood Security - Jasnirani, R.; Krishnan, R. (Current Science, 2024)
Agricultural researchers have identified low-external input sustainable agriculture as a preferred development approach to address food security challenges. Recent years have seen the introduction of several sustainable agriculture systems, including inte
Keywords: Livelihood Security; Organic- Inputs; Small-Scale Farmers; Institutional Linkage